2019
DOI: 10.1177/1460458219881333
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of medical concepts in question and answering of health communities

Abstract: The ability to automatically categorize submitted questions based on topics and suggest similar question and answer to the users reduces the number of redundant questions. Our objective was to compare intra-topic and inter-topic similarity between question and answers by using concept-based similarity computing analysis. We gathered existing question and answers from several popular online health communities. Then, Unified Medical Language System concepts related to selected questions and experts in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Machine and deep-learning approaches based on sentiment and semantic analysis are popular methods of analysing textcontent in online health forums. Many researchers have used these methods on social media such as Twitter, reddit [2]- [7], and health information websites [8], [9]. For example; Halder and colleagues [10] focused on exploring linguistic changes to analyse the emotional status of a user over time.…”
Section: Related Workmentioning
confidence: 99%
“…Machine and deep-learning approaches based on sentiment and semantic analysis are popular methods of analysing textcontent in online health forums. Many researchers have used these methods on social media such as Twitter, reddit [2]- [7], and health information websites [8], [9]. For example; Halder and colleagues [10] focused on exploring linguistic changes to analyse the emotional status of a user over time.…”
Section: Related Workmentioning
confidence: 99%
“…20 These websites provide a venue for consumers to seek experiential information from other users for a quick solution to their healthcare concerns. 21 It has previously been observed that Q&A platforms offer a valuable opportunity to better understand users' information needs and concerns about various health issues. 22 Text mining has been introduced as a useful method for studying the health information needs in Q&A forums from different perspectives.…”
Section: Health Information Needs On Question-and-answer Forumsmentioning
confidence: 99%
“…Machine and deep-learning approaches based on sentiment and semantic analysis are popular methods of analysing text-content in online health forums. Many researchers have used these methods on social media such as Twitter, reddit [2] - [7], and health information websites [8], [9]. For example; Halder and colleagues [10] focused on exploring linguistic changes to analyse the emotional status of a user over time.…”
Section: Introductionmentioning
confidence: 99%